AKRAB PEMANFAATAN MEDIA ONLINE SEBAGAI MEDIA KOMUNIKASI DALAM MENCIPTAKAN BRAND IMAGE BAGI BISNIS ONLINE EGYPTIAN CREAM DI ERA DIGITAL: Studi Kasus tentang Pemanfaatan Media Online Sebagai Media Komunikasibagi Bisnis Online UKM Egyptian Cream di Bandung - Ditha Prasanti Kismiyati El Karimah (Jurnal Ilmu Komunikasi AKRAB, 2017)
ABSTRACTOnline media is familiar in everyday life. In this modern era, online media has also grown increasingly rampant in Indonesia. Almost every individual did not escape his daily using online media. Online media can be regarded also as a medium of communication used in the best-selling success factors in the communication process. In this study, success in question is create a brand image of a product of SMEs. One area of successful UKM and succeeded thanks to online media are Egyptian Cream. Egyptian Cream is a skincare brand that was founded in June 2010 by Restiani Nur Fauzi. The concept of products offered by the Egyptian herbal skincare cream is made from bees, such as honey, royal jelly, propolis and beeswax. The main products offered in this line of business is Egyptian Magic Cream directly imported from Washington DC. As the first hand of the producer, quickly mastered the Egyptian Cream Egyptian Magic Cream market in Indonesia. This is a good business slit on the sidelines of facial whitening products are popping up when it is considered by people who want herbal skin care products are safe. In this study, researchers used a qualitative approach with case study method. Data collection techniques used were interviews, observation and documentation. Data analysis technique used is perseverance observation, triangulation of data, and adequacy referential. The results of this study indicate that the use of online media to the Egyptian Cream is highly optimized, this business line has been using online media to 9 types. This encourages a high increase in turnover in the sale of products Egyptian Cream.Keywords:Utilization, Online Media, Brand Image, Egyptian Cream